Evaluation of pharmacokinetics and pharmacodynamics of sinomenine-hyaluronic acid conjugate after intra-articular administration for osteoarthritis treatment - Liu J; Shao H; Fang S; Cheng Y; Ling P; Chen J (Drug Design, Development and Therapy, 2019)
Jie Liu,1,2,* Huarong Shao,1,* Shaoying Fang,1 Yanling Cheng,1 Peixue Ling,1,3 Jianying Chen1,3 1Key Laboratory of Biopharmaceuticals of Shandong Province, Shandong Academy of Pharmaceutical Sciences, Jinan, Shandong Province, China; 2Shandong Provincial Engineering Research Center for Medicines of Orthopedic Pain, Shandong Mingren Freda Pharmaceutical Co. Ltd, Jinan, Shandong Province, China; 3Key Laboratory of Mucosal and Transdermal Drug Delivery Technology in Shandong Province, Shandong Freda Pharmaceutical Group Co. Ltd, Jinan, Shandong Province, China *These authors contributed equally to this work Objectives: Intra-articular injection of sinomenine (SN) is an effective treatment method for knee osteoarthritis (OA), however, SN could be eliminated quickly in vivo. To extend the residence time of SN in the joint cavity, the SN-hyaluronic acid (HA) conjugate was prepared previously. This study was performed to evaluate the pharmacokinetics and pharmacodynamics of SN-HA conjugate after intra-articular administration for the treatment of OA. Methods: A high performance liquid chromatography-mass spectrometry (HPLC-MS/MS) method was established to determine the SN content in rat synovial fluid. One hundred and twenty rats were randomly divided into two groups, the SN-HA group and SN group. The concentration of SN in articular cavity washings was determined by HPLC-MS/MS. The protective effect on the cartilage was evaluated by histological evaluation in a model of papain induced rabbit knee osteoarthritis. Results: The method was validated with respect to sensitivity, specificity, linearity, precision, accuracy and especially the stability of analytes under various conditions, and was successfully applied in evaluating the pharmacokinetic profiles of SN in the joint cavity. Compared to the SN injection, the drug exposure in joint cavity was significantly increased following SN-HA injection administration, and AUC(0–12h) was 2.9 times of SN injection, mean residence time (MRT) was 1.88 times of SN injection. In the pharmacodynamic study, there was no significant difference between the SN-HA twice-treated group and SH/HA five-times mixture-treated group. Conclusion: The local bioavailability of SN in joint cavity was improved significantly after conjugated with HA. The SN-HA conjugate showed good synergism effect of OA inhibition. The results indicated that the SN-HA conjugate seemed to be an effective therapeutic means for the treatment of OA. Keywords: sinomenine-hyaluronic acid conjugate, HPLC-MS/MS, pharmacokinetics, pharmacodynamics, osteoarthritis